Perceptions of the learning and emotions of students of economic sciences in pandemic: Contributions to the virtualization of higher education (Costos y Gestión, 2023)
This paper aims to analyze the perceptions of virtual learning and emotions of students from the Faculty of Economic Sciences of the National University of Río Cuarto (Argentina) during the health emergency caused by COVID-19. In order to fulfill this objective, a qualitative research approach was used through which a descriptive study was carried out, in which a questionnaire on academic trajectories was used as the main source for data collection. The results reveal positive appreciations of the teaching proposals, as well as positive appreciations about the greater flexibility to organize the study and the time available and the comfort that this provides. In contrast, virtual teaching was accompained by connectivity problems, less interaction and inconveniences for self-organization. The evidence obtained is an important input to work in the future on the design of learning contexts that favor an improvement in the performance of Economic Sciences students, which could be achieved through hybrid work proposals that would allow taking advantage of the benefits that virtual teaching reports.
Keywords: perceptions of the learning; emotions; university students; Economic Sciences; remote teaching during COVID-19 pandemic